Globalizing the Academic Presidency: Competing for Talented Leadership - Skinner, Richard A. (International Higher Education, 2018)
For more than half a century, globalization has been a powerful force in almost every aspect of contemporary life. The search for talent in some sectors is now global in scope. Higher education shows signs of the same force at work in some universities’ searches for leadership. Two examples are provided and conjectures offered as to why this may continue with academic presidents.